The willow whistle - Meigs, Cornelia, 1884-1973 (The Macmillan Company, 1931)
"Little Mary Anne, a child of the American frontier, is the heroine of this tale of pioneer days in the Middle West. Mary Anne and her friend Eric Thorveg make friends with some of the Indians, notably Chief Gray Eagle, and this often stands them in good stead." Book rev. digest.